Using Social Cognitive Theory to Determine Factors Predicting Nutritional Behaviors in Pregnant Women Visiting Health Centers in Tabriz, Iran - Motahhareh Jalily; Majid Barati; Saeed Bashirian* (Hamadan University of Medical Sciences, 2015)
Background and Objectives: Women's nutrition during pregnancy is a key determinant of maternal and fetal health. Therefore, the current study used the Social Cognitive Theory (SCT) to determine factors predicting the nutritional behaviors of pregnant women in Tabriz, Iran. Materials and Methods: This analytic study applied multistage random sampling to select 380 pregnant women who visited health centers in Tabriz during 2014. Data were collected using the Nutritional Behavior Questionnaire and a researcher-made questionnaire on the constructs of the SCT (knowledge, outcome expectations, outcome expectancies, self-efficacy, social support, and self-regulation). The questionnaires were completed through interviews and self-report. Pearson's correlation and liner regression analyses were performed to analyze the data in SPSS20. Results: The participants' mean age was 27 years. Among the different constructs of the SCT, outcome expectations (P =0.039), outcome expectancies (P=0.046), knowledge (P=0.043), and self-regulation (P=0.001) had significant roles in explaining the variance in nutritional behaviors of pregnant women. These factors could in fact predict 16% of the variance in nutritional behavior. Bread and cereals, meat and beans, fruits, and vegetables consumption were below the recommended level in 54.5%, 73.2%, and 55.3%, and 70.5% of the subjects, respectively. Conclusion: Based on our findings, knowledge, outcome expectations, outcome expectancies, and self-regulation can be used in the development of educational interventions to promote healthy nutritional behaviors in pregnant women.